Demulsifying water-in-oil emulsions by ethyl cellulose demulsifiers studied using focused beam reflectance measurement. (7th July 2015) - Chen, Zhuqi; Peng, Junxia; Ge, Lingling; Xu, Zhenghe
Abstract: Removal of residual water droplets from produced fluids of petroleum is a challenging task because the emulsified water droplets with size of a few micrometers are extremely stable. A focused beam reflectance measurement (FBRM) was used for on-line monitoring of emulsified water droplet size distribution in petroleum emulsion systems and chemical demulsification process. After establishing the feasibility of using FBRM to measure droplet size distributions in petroleum emulsions, factors influencing the average size of water droplets were investigated to evaluate the demulsification dynamics by ethyl cellulose demulsifiers. The FBRM is proven to be a valuable tool for monitoring demulsification process in situ in real time to understand demulsification mechanisms, which sheds the lights on improving the current technology of demulsifying water-in-oil emulsions of petroleum industry. Highlights: Quantitative on-line monitor of water-in-oil emulsion size distributions using FBRM. Evaluation on demulsification dynamics by on line droplet size distribution measurement. Quantification of factors influencing size distribution of emulsified water droplets by ethyl cellulose demulsifiers. Demonstration of more rapid flocculation process than coalescence by polymeric chemical demulsifiers. Phenomenological model of demulsifying water in diluted bitumen emulsions by ethyl cellulose demulsifiers.